PENGEMBANGAN PALUDARIUM SEBAGAI MEDIA PEMBELAJARAN BIOLOGI POKOK BAHASAN EKOSISTEM DI SMA - Ratna Komala; Ade Suryanda; Diana Dia Lismana (Universitas Negeri Jakarta, 2016)
Paludarium is one the art of landscape design in a container with visualizing terrestrial ecosystem, aquatic ecosystem, and air ecosystem, so looks like a real in nature. Paludarium can be potential as a media of learning ecosytem. The aims of this research was to develop paludarium as Biology learning media on the subject of ecosystem and know the feasibility of paludarium as learning media. The research was held at Senior High School 38 Jakarta with using research and development method. Analysis of potential and problems, paludarium design, validation design, paludarium revision, paludarium try out were the steps in the research. Paludarium received the average score was 84,2% that achieved good interpretation. The average value to limited field try out (36 students) of the test after using paludarium was 82.77. The average value to wide scale field try out (72 students) of the test after using paludarium was 83.54. The mastery of classical learning to limited field try out after using paludarium was 97.2% and to wide scale field try out after using paludarium was 81.9%. The result of this research showed that the paludarium could be utilized as one of Biology learning media on the subject of ecosytem at senior high school.